Digital dilemmas : power, resistance, and the Internet - Franklin, Marianne, 1959- (Oxford University Press, 2013)
Digital Dilemmas looks at the dynamics of power and resistance surrounding the internet. It focuses on how publics, nation-states, and multilateral institutions are being continually reinvented in local and global decision-making domains that are accessed and controlled by a relative few. Importantly it unpacks the ways in which computer-mediated power relations play out as ""on the ground"" and ""cyberspatial"" practices and discourses that collude and collide with one another at the personal, community, and transnational level. Case studies include homelessness and the internet, rights-based